Dermoscopic and clinical features of halo nevus in children - Rong CAO; Yuanyuan CHAI; Hui LU; Hua QIAN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To study the dermoscopic and clinical features of halo nevus in children. Methods We retrospectively analyzed the clinical data, including general condition, clinical features, family history and dermoscopic data of 110 patients with halo nevus in our hospital from January 2019 to February 2023. Results The mean age of 110 patients was (8.91±3.26) years. The ratio of male to female was 1.29∶1. Involvements on the face and neck accounted for 32.82%, and 40.00% of patients were complicated with vitiligo. The incidence of multiple halo nevi was higher in patients with vitiligo than in those without vitiligo (χ2=8.61, P=0.003). Among the 45 cases with a family history, the proportion of individuals with family history was higher in patients with vitiligo (7/22, 31.82%) than in those without vitiligo (1/23, 4.35%) (χ2=4.08, P=0.043). The most common dermoscopic features of central nevi were homogeneous pattern (21 cases, 36.84%) and globular pattern (10 cases,17.54%). The peripheral halo often presented as structureless hypopigmentation (36 cases,63.16%). Improvement was observed in 70.00% of the patients after 6-month treatment with oral compound glycyrrhizin tablets plus topical glucocorticoids/0.03% tacrolimus ointment. The proportion of patients without autoimmune diseases was lower in effective cases than in the ineffective cases (χ2=5.70, P<0.05). ConclusionsHalo nevus mainly occurs on the face and neck, with no gender difference. The incidence of vitiligo is higher in patients with halon nevus. The most common dermoscopic pattern of the central nevus is homogeneous or globular pattern, and the peripheral halo commonly shows structureless hypopigmentation rim. Oral drugs combined with topical drugs are effective in the treatment of halo nevus in children.